Asymmetric Assembly of Steroidal Tetracyclic Skeletons12. Issue 36 (9th October 2014) - Gupta, Preeti; Panda, Gautam
Abstract: Steroids have long played a vital role in organic synthesis because of their unique structural motif and associated biological properties. In recent years, asymmetric synthesis has emerged as a powerful tool for assembling the tetracyclic framework with high levels of molecular diversity. This review summarizes the latest developments in the enantioselective syntheses of both natural and synthetic steroids incorporating the carbocyclic skeleton. The approaches to the synthesis of steroids and related molecules are based primarily on the use of chiral starting materials, the employment of reagent‐controlled asymmetric induction assisted by chiral complexes, chiral Lewis acids or organocatalysts, or the utilisation of chiral auxiliaries. Abstract : The review highlights recent advances in the enantioselective synthesis of carbocyclic steroidal skeletons. Various synthetic approaches based on the use of chiral starting materials, reagent‐controlled asymmetric induction and asymmetric synthesis with the aid of chiral auxiliaries are discussed.